2014
DOI: 10.1007/s12206-014-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of a novel compact power generation and waste heat operated absorption, ejector-jet pump refrigeration cycle

Abstract: An R-152a ejector-jet pump refrigeration cycle and a LiBr-H 2 O absorption refrigeration cycle have been integrated with a renewable energy power generator for making a proposed 'novel compact cogeneration cycle'. The exergy analysis of this proposed cycle leads to a possible performance improvement. Nearly 71.12% of the input exergy is destructed due to irreversibilities in the different components. The useful exergy output is around 7.12%. The exhaust exergy lost to the environment is 21.76%, which is lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Khaliq et al [298] investigated a coupled power and EAbRS: the coupled systems provide approximately 22.7% of the input exergy and 19.7% of the input energy available as the useful output. Finally, Kumar [299] investigated an EAbRS using an R-152a ejector on cycle and a LiBr-H 2 O absorption cycle integrated with a renewable energy power generator. The useful exergy and energy output are approximately 7.12% and 19.3%, respectively.…”
Section: Eabrs Combined With a Power Cyclementioning
confidence: 99%
“…Khaliq et al [298] investigated a coupled power and EAbRS: the coupled systems provide approximately 22.7% of the input exergy and 19.7% of the input energy available as the useful output. Finally, Kumar [299] investigated an EAbRS using an R-152a ejector on cycle and a LiBr-H 2 O absorption cycle integrated with a renewable energy power generator. The useful exergy and energy output are approximately 7.12% and 19.3%, respectively.…”
Section: Eabrs Combined With a Power Cyclementioning
confidence: 99%
“…Efficiency improvement of a similar cycle combining a LiBr-H2O absorption and an ERS powered by renewable energy was later conducted by Kumar and Kumar [324] on the basis of an energy and exergy approach. It was concluded that coupling a well designed jet pump with a conventional absorption system favourably affected exergy and energy efficiencies.…”
Section: Of 73mentioning
confidence: 99%
“…The possible application of such device in absorption systems with water as refrigerant was studied in Ref. [5]. The performance of the vapoureliquid ejector and the refrigeration cycle were studied using numerical modelling.…”
Section: Introductionmentioning
confidence: 99%